Estudos termodinâmico e biodegradação de embalagens a base de amido de mandioca e agentes naturais antioxidantes - Cotta, Anômora Ariane Rochido dos Santos (2022)
The use of petroleum-based materials and their current processing techniques have caused problems related to our finite resources and the environment. Alternatively, scientists have been developing new technologies, such as active biodegradable packaging derived from polymers from natural sources and natural agents antioxidants, to minimize the problems generated by fossil-based packaging and toxic chemical sources. The objective of this work is to perform thermodynamic and physics studies of active biodegradable packaging based on cassava starch and natural antioxidant agents (lycopene). This research was divided into three stages. In the first stage, the biodegradation of packaging in the soil was studied. The samples were placed on an aluminum screen and inserted into the soil at a depth of 4 cm for approximately 18 days. The biodegradation of the films was determined through Fourier Transform Infrared Spectroscopy (FTIR), and visual analysis. The subsequent step was to perform the water solubility analysis, where the samples were completely submerged in deionized water under agitation for a time of 24 hours, the solubility was determined through the percentage of solubilized material. The third stage is related to the determination of water sorption isotherms and thermodynamic parameters. The isotherms describe the relationship between the water activity and the equilibrium moisture content of the material at a constant temperature, being represented graphically. Through the thermodynamic parameters, it is possible to extract information about the stability of the packaging, as well as about the spontaneity or not of the water adsorption process. To obtain the water sorption isotherms and thermodynamic properties, the packages were analyzed under different temperature conditions ranging from 5ºC, 15ºC, and 25ºC in different saline solutions until the samples reach a constant weight. After reaching equilibrium, it was possible to determine the moisture content absorbed and the thermodynamic properties of the packaging. From the results obtained it was possible to verify the biodegradation of the packages through visual observations and FTIR analysis. The effect is observed through different aspects present in the packaging, such as the roughness of the film surface, the formation of holes or cracks, fragmentation, color changes, or the variation in mass due to interaction with the imposed atmosphere. In addition, biodegradation can cause changes in the structure of the films that were observed by FTIR. Regarding the water solubility analysis, the percentage decreases with the addition of lycopene in the polymer matrix. For the analysis of water sorption isotherm, the best mathematical adjustment is found to estimate the monolayer humidity values (Xm) with increasing temperature, done by applying the GAB model. Finally, through the thermodynamic analysis, it was possible to visualize that both the ΔHdif and the -ΔSdif differential curves increased exponentially for all samples with increasing moisture content until values were close to zero, and the occurrence of enthalpy compensation entropy was confirmed with entropy driving the adsorption process.